Nutrient value of landfill leachate on the growth of Brassica rapa L. - Alaribe, Frank O; P, Agamuthu (Malaysian Journal of Science, 2010)
Leachate from Ampar Tenang landfill was characterized and then treated with ferric chloride. Treated leachate was used at different dilution levels as biofertilizer for the cultivation of Brassica rapa L. (leafy vegetable). A treatment with inorganic fertilizer at the same N-equivalent as the leachate, and a control (water) were also included. Physical growth parameters (leaf length, leaf width, stem height) and harvest parameters (total number of leaves, root length and dry weights of different plant parts) were determined. The dry-weights of leaf, root and stem in (both) treatments had significantly higher biomass over the control. B. rapa receiving 25%DTL had the highest specific growth rate for leaf length (0.53 mm/d) and leaf width (0.39 mm/d). Heavy metal accumulations in B. rapa grown with leachate and in B. rapa bought from the market were compared with the permissible concentration limit of FAO/WHO. Inorganic fertilizer did not give a better fertilizing effect in terms of plant yield and growth than the leachate treatments according to this study, but heavy metal accumulation makes the leachate unfit for fertilization of edible plants like Brassica rapa L.